2021
DOI: 10.12944/cwe.16.2.12
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Chemistry at Deep Aquifer in Koyra: Khulna, Bangladesh

Abstract: Koyra (Khulna District) is the coastal Upazila of Bangladesh and is very susceptible to salinity intrusion. The surface and shallow tube well water in the Upazila is naturally saline. The quality of subterranean tube well water in the deliberate area is hardly presented for different Unions of Koyra. Dakshin Bedkashi Union of Koyra is very saline prone. Therefore, the groundwater chemistry of Dakshin Bedkashi Union was determined to legalize if the groundwater is fit for drinking and irrigation or not. Spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Besides, Bangladesh experience altered rainfall patterns and increased flood frequency that causes saltwater intrusion in coastal regions, which consequently contaminate GW resources [ 59 ]. Numerous studies have recently confirmed the degradation of WQ in various coastal regions of Bangladesh, including Satkhira [ 60 ], Khulna [ 61 , 62 ], Patuakhali [ 63 ], Gopalganj [ 64 , 65 ] and Jashore [ 66 ]. However, being the only island district of Bangladesh, the GW resources of Bhola have gained lesser attention of the scientific community in terms of rating GW state.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Bangladesh experience altered rainfall patterns and increased flood frequency that causes saltwater intrusion in coastal regions, which consequently contaminate GW resources [ 59 ]. Numerous studies have recently confirmed the degradation of WQ in various coastal regions of Bangladesh, including Satkhira [ 60 ], Khulna [ 61 , 62 ], Patuakhali [ 63 ], Gopalganj [ 64 , 65 ] and Jashore [ 66 ]. However, being the only island district of Bangladesh, the GW resources of Bhola have gained lesser attention of the scientific community in terms of rating GW state.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous types of research have been performed to verify the water quality in different coastal parts of Bangladesh, e.g., Satkhira [8,24,28], Khulna [29,30], Patuakhali [31], Gopalganj [32,33], Jashore [7,[34][35][36][37][38][39][40], and central south parts of Bangladesh [31,41]. Not only has those, but also the water quality been determined in other parts of The changing climate may have impinged on the cropping pattern of Bangladesh from the primeval period [6].…”
Section: Introductionmentioning
confidence: 99%